THE USE OF MEDIA BASED ON THE THEME OF SCHOOL HYGIENE IN 61 STATE PRIMARY SCHOOLS OF BANDA ACEH CITY - Khairunnisa; Ika Ramasari; Jessica Astiana; zahratul Idami; Lindri Novia (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses descriptive qualitative research methods. Namely researchbased on the phenomenon that occurred in one case at SD Negeri 61 BandaAceh. Based on the facts seen in the school that teachers still useold/conventional methods in the thematic learning process, thematic learningwhich integrates various subjects in one theme or topic, allows students tounderstand the relationship between concepts as a whole. Researchers observethe learning carried out by elementary school teachers Negeri 61 Banda Aceh,in fact, thematic learning really provides opportunities for teacher creativity inthe active learning process and can also facilitate the process of students'understanding and the learning process carried out by teachers at school.Through this research method, it will be explained transparently to produce theapplication of integrative thematic learning using a causal study. It is knownthat the curriculum used in this school is that some classes still use theindependent learning curriculum, namely only in classes 1 and 4, some still usethe old curriculum, namely K13, so that the learning process carried out is quitedifferent and not significant to the results obtained by students in integrativethematic learning.